Pendidikan Karakter Holistik Integratif di PAUD Terpadu ‘Aisyiyah Nur’aini Ngampilan Yogyakarta - Widodo, Hendro; Risti P, Avanti Vera (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2017)
This study aims to determine: 1) The basis of character education holistically and integratively in Early Childhood Nuraini; 2) The PAUD program environment is developed for the development of character education in a holistic and integrative manner; 3) actions and actions of educators in their role of developing character education holistically and integratively, and 4) parent involvement in the character education model holistically and integratively.The results of this study can be summarized as follows: 1) Moral Education Platform, Moral, Holistic and Integrative Character in Integrated Early Childhood 'Aisyiyah Nur'aini uses the foundation of religion, local culture and objective values ​​of the nation. Character values ​​can be taught systematically in the Holistic character education model as follows: a) Habituation (good habituation and culture), b) learning good things (mora, knowing), c) morale Feeling and loving: feeling and loving good, d) moral acting (good action), and e) model (moral model) of the surrounding environment; 2) the environment here is divided into the physical and social environment. In view of the physical environment shows the lack of school lighting due to the geographic conditions of schools located in the lowlands and surrounding there are level buildings so that the school conditions seem dark or lack of open lighting. Non-physical environment is seen from the interaction of all teachers in developing character education in an integrative holistic way. Implementation of character education is done every day in the classroom through habituation (habituation) with modeling of teachers with 5K requirements (consensus, commitment, consistent, continuous and consequent); 3) The teacher's action is to integrate the child's character in integrated intellectual, moral and physical development; and 4) parental involvement in character education through parenting education and parenting class activities.